2008
DOI: 10.1007/s11340-008-9172-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mesostructure, Mechanical Behaviour and Damage of Cement Composites Under High-Pressure Confinement

Abstract: This work seeks to determine how the mesostructure of seven types of cement composites containing alumina particles or not controls their deviatoric strength, compaction law, and damage under high-pressure of confinement. First, the method of analysis of quasioedometric compression tests is presented. Accuracy of the method for concrete is discussed by means of numerical simulations. The confined compression tests performed show the effects of adding ceramic aggregates. Furthermore, an application of post-mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A method was proposed previously to process experimental data of quasi-oedometric compression tests [8,10,11]. Its aim is to compute the mean radial stress and strain levels within the specimen from the records of strain gauges located on the outer surface of the cell.…”
Section: Methods Used To Process the Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A method was proposed previously to process experimental data of quasi-oedometric compression tests [8,10,11]. Its aim is to compute the mean radial stress and strain levels within the specimen from the records of strain gauges located on the outer surface of the cell.…”
Section: Methods Used To Process the Experimental Datamentioning
confidence: 99%
“…Gatuingt [15] performed dynamic tests with cells made of steel or brass. Forquin et al [8,10] proposed an analysis of the experimental data taking account of the shortening of specimen and of a possible plastic deformation of the confining cell. More recently, dynamic QOC tests performed with a Split Hopkinson Pressure Bar device were analysed applying the previous methodology [11].…”
Section: Static and Dynamic Quasi-oedometric Compression Testsmentioning
confidence: 99%
“…Twenty cube compression tests on the C20/25 concrete showed that the scatter is fairly low. If smaller cubes were produced, either by casting in a smaller mould or by cutting larger samples, then they would surely produce a larger scatter than the larger cubes as the variation from one point in the concrete to the next can be quite large due to the aggregate, air content, degree of hydration and various other parameters [60][61][62]. The C20/25 concrete was also tested at various stages of curing.…”
Section: Materials Testsmentioning
confidence: 99%
“…Burlion et al [11], for instance, developed an instrumented elastic steel vessel. Forquin et al [12][13][14] proposed a new analysis of experimental data taking account of the shortening of specimen and of a possible plastic deformation of the confining cell. More recently, dynamic QOC tests have been performed with a split-Hopkinson pressure bar device in the range of strain-rates from 80 to 200/s applying the previous methodology [15][16].…”
Section: Principlementioning
confidence: 99%